2023
DOI: 10.1186/s42397-023-00154-x
|View full text |Cite
|
Sign up to set email alerts
|

High day and night temperatures impact on cotton yield and quality—current status and future research direction

Dinesh K. Saini,
S. M. Impa,
Donna McCallister
et al.

Abstract: Heat waves, and an increased number of warm days and nights, have become more prevalent in major agricultural regions of the world. Although well adapted to semi-arid regions, cotton is vulnerable to high temperatures, particularly during flowering and boll development. To maintain lint yield potential without compromising its quality under high-temperature stress, it is essential to understand the effects of heat stress on various stages of plant growth and development, and associated tolerance mechanisms. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Despite cotton's inherent plasticity in its growth response to environmental conditions [41], primarily due to its indeterminate growth habit, its ability to grow and produce bolls is constrained by specific temperature ranges [42]. Saini et al [18] reported that while cotton is well adapted to semiarid regions, it remains vulnerable to high temperatures, particularly during the critical stages of flowering and boll development. Cotton achieves greater fiber length during boll development at 22 °C, with a decline observed at both lower and higher temperatures [42], while fiber strength is enhanced when temperatures exceed 25 °C during this stage [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite cotton's inherent plasticity in its growth response to environmental conditions [41], primarily due to its indeterminate growth habit, its ability to grow and produce bolls is constrained by specific temperature ranges [42]. Saini et al [18] reported that while cotton is well adapted to semiarid regions, it remains vulnerable to high temperatures, particularly during the critical stages of flowering and boll development. Cotton achieves greater fiber length during boll development at 22 °C, with a decline observed at both lower and higher temperatures [42], while fiber strength is enhanced when temperatures exceed 25 °C during this stage [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant dependence of quality on environmental conditions, it is crucial to understand the effects of various climatic factors across different cotton-growing regions on fiber quality traits. Various studies have explored the impact of environmental factors on fiber quality traits [3,17,18]. Among these factors, water limitation and drought conditions are considered the primary environmental constraints on fiber quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Implementing efficient irrigation methods such as drip or micro-sprinkler systems to optimize water use and minimize water loss [67]. Employing soil conservation practices like mulching and conservation tillage to enhance soil water retention and reduce evaporation [68]. Identifying the impact of drought stress on cotton and applying effective ways to mitigate its effects is critical for assuring sustainable cotton production, safeguarding yields, and sustaining fiber quality.…”
Section: Impact Of Drought Stress On Cottonmentioning
confidence: 99%
“…Implementing efficient irrigation methods such as drip or micro-sprinkler systems to optimize water use and minimize water loss [67]. Employing soil conservation practices like mulching and conservation tillage to enhance soil water retention n and reduce evaporation [68].…”
Section: Advanced Biotechnological Interventions In Mitigating Abioti...mentioning
confidence: 99%
“…There are numerous studies on cotton cultivation in terms of its environmental impact (the use of pesticides, water consumption, and soil degradation), agronomic approaches, the phenological and physiological aspects of cotton growth and development, cotton cultivation during climate change, sustainable cotton production and organic cotton, the effects of air pollution on cotton fabric, cotton breeding and genetics, cotton yield and quality, the utilization of cotton, the cotton market, etc. [26,29,[33][34][35][36][37]. However, no published studies were found on the effects of technogenic air pollution on the biochemical composition of cotton grown in the immediate vicinity of a nitrogen-phosphate fertilizer factory.…”
Section: Introductionmentioning
confidence: 99%